Identification of Information and Communication Technologies’ (ICTs) Needs regarding Professional Development and Modern Teaching Methods for Madarassa Teachers - Mohiman, Ata Ul; Ullah, Naeem; Zafar, Jam Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The study aimed to analyze, “Identification of Information and Communication Technologies (ICTs) Needs regarding Professional Development and Modern Teaching Methods for Madarassa Teachers”. The study was survey and descriptive in nature. The QUAN-qual technique was adopted. The explanatory sequential technique was used. The stratified sampling technique was adopted. The 30 students of madarassa, 3 madarassa’s instructors and one Mohtamim from each of 2 madarassas of all 9 divisions of Punjab. The 2 deoband madarassas were equally selected from each division of Punjab. The questionnaire based on Likert scale and interview protocol based on an open-ended item. The validity of questionnaire was ensured through experts’ opinion and reliability of was calculated through Cronbach Alpha using SPSS-20. The study concluded that majority of students of Shahadat ul alia and Shahadat ul almia viewed that ICTs make it easy to ensure online presence, access to internationally trained teachers facilitates learning methods as a modern teaching style. The study recommended that ICT may be included in teachers’ professional development for effective training and learning of Madrassas’ instructors.